2017
DOI: 10.5597/00223
|View full text |Cite
|
Sign up to set email alerts
|

First estimate of common bottlenose dolphin (Tursiops truncatus) (Cetacea, Delphinidae) abundance off Uruguayan Atlantic coast

Abstract: The common bottlenose dolphin Tursiops truncatus is often observed throughout the oceanic coast of Uruguay. Historically, its distribution was wider, including the estuary of the Río de la Plata, but currently its occurrence seems to be restricted mainly to the Uruguayan Atlantic coast (Rocha Department). Conflicting interests and tradeoffs between conservation and development are being generated in Uruguay. On one hand, the establishment of protected areas, responsible tourism and sustainable fisheries are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…On the other hand, remarkably low levels of genetic diversity for the coastal ecotype likely reflects small population sizes of possibly a few hundred individuals (Fruet, Flores, et al., ; Fruet, Zappes, et al., ). Mark‐recapture data from long‐term studies of coastal populations along the SWA indicate critical small population sizes (populations not exceeding 90 individuals) and high site fidelity of individuals (e.g., Daura‐Jorge, Ingram, & Simões‐Lopes, ; Fruet, Daura‐Jorge, Möller, Genoves, & Secchi, ; Giacomo & Ott, ; Laporta, Fruet, et al., ; Vermeulen & Cammareri, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, remarkably low levels of genetic diversity for the coastal ecotype likely reflects small population sizes of possibly a few hundred individuals (Fruet, Flores, et al., ; Fruet, Zappes, et al., ). Mark‐recapture data from long‐term studies of coastal populations along the SWA indicate critical small population sizes (populations not exceeding 90 individuals) and high site fidelity of individuals (e.g., Daura‐Jorge, Ingram, & Simões‐Lopes, ; Fruet, Daura‐Jorge, Möller, Genoves, & Secchi, ; Giacomo & Ott, ; Laporta, Fruet, et al., ; Vermeulen & Cammareri, ).…”
Section: Discussionmentioning
confidence: 99%
“…These coastal populations are small (<100 individuals) and associated with estuaries, river mouths, and lagoons (see Simões‐Lopes, ; Lodi et al., ; Laporta, et al., ; Fruet, Flores, & Laporta, ; Fruet et al., ; for reviews). Sighting data suggest no movement of coastal bottlenose dolphins to deep waters (i.e., >20 m depth), although movements of individuals between coastal areas frequently occur (Würsig, ; Simões‐Lopes & Fábian, ; Laporta, Di Tullio, et al., ; Laporta, Fruet, & Secchi, ). Recent studies have shown remarkably low levels of genetic diversity and strong genetic differences among these coastal populations at both microsatellites and mitochondrial DNA markers (Costa et al., ; Fruet et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…(2016) suggested that the species has a continuous distribution along the Brazilian coast, which varies in depth from 1.6–50 m, as reported by Laporta et al . (2016). The group sizes detected in the present work (mean 39 ± 22 individuals, N = 13) were higher than those previously observed in other regions of the Brazilian coast.…”
Section: Discussionmentioning
confidence: 99%
“…Bottlenose dolphins occur year-round in the Atlantic coastal waters of Uruguay, using the coastal zone mainly for feeding, socialising and reproduction (Fruet et al, 2014;Laporta et al, 2016;Menchaca et al, 2019;Ott et al, 2016;Tellechea et al, 2014). Groups are variable in size and age composition, ranging from one to 30 individuals, with larger groups also including calves (Laporta et al, 2016;Menchaca et al, 2019;Tellechea et al, 2014).…”
Section: Study Areamentioning
confidence: 99%